2022
DOI: 10.3390/ma15155187
|View full text |Cite
|
Sign up to set email alerts
|

Ag Nanocluster-Enhanced Scintillation Properties of Borophosphate Glasses Doped with CsPbBr3 Quantum Dots

Abstract: A novel and effective method to improve scintillation properties of glass-ceramics, such as intensity enhancement and decay-time shortening, is reported in this work. Compared with crystal scintillators, glass scintillators always have the problems of low efficiency and long decay; how to solve them has always been a scientific puzzle in the field of scintillation glass-ceramics. The plasma enhancement effect can be predicted to solve the above problems. Ag+ ions were diffused into glasses by ion exchange, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Due to the plasma enhancement effect, the luminous intensity of quantum dots is increased by 6.25 times. [ 100 ] Eu was doped into borosilicate glass, which optimized the crystallization of quantum dots, thus significantly improving the imaging resolution. [ 21 ] In order to shorten the decay time, a high refractive index borosilicate glass matrix was employed, which effectively improved the radiation recombination rate of nanocrystals and reduced the decay time to 15.2 ns.…”
Section: Glass Scintillator Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the plasma enhancement effect, the luminous intensity of quantum dots is increased by 6.25 times. [ 100 ] Eu was doped into borosilicate glass, which optimized the crystallization of quantum dots, thus significantly improving the imaging resolution. [ 21 ] In order to shorten the decay time, a high refractive index borosilicate glass matrix was employed, which effectively improved the radiation recombination rate of nanocrystals and reduced the decay time to 15.2 ns.…”
Section: Glass Scintillator Materialsmentioning
confidence: 99%
“…Du et al diffused Ag + into the borophosphate CsPbBr 3 quantum dot glass, reducing the decay time to half of the original value (Figure 7b). [ 100 ] Recently, several groups have conducted researches on long‐term stability. [ 72,99,108,109 ] Among them, CsPbBr 3 nanocrystals borosilicate glass showed excellent stability to water and heat, while CdS quantum dot embedded borosilicate glass ceramics also exhibited good irradiation stability, moisture and heat resistance.…”
Section: Detection Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al added Ag into borophosphate glass. The PL intensity of CsPbBr 3 quantum dot glass was increased by 3 times, and its radioluminescence intensity was increased by 6.25 times . Numerous studies have demonstrated that the incorporation of noble metal nanoparticles into glass systems can realize the excitation of plasmons, resulting in a localized surface plasmon resonance effect (LSPR). As noble metal nanoparticles aggregate, their localized surface plasmon resonances become mutually coupled, leading to the emergence of the Purcell effect .…”
Section: Introductionmentioning
confidence: 99%